Simultaneous determination of 11 kinds of siloxanes in drinking water and source water using solid-phase microextraction combined with gas chromatography-mass spectrometry - Liu, Sijie; Ma, Jie; Jiang, Su (Frontiers in Chemistry, 2025)
BackgroundSiloxanes have been widely used in various products and have been detected to varying degrees in the environment. It has been reported that methylsiloxane has toxic effects on the nervous, immune and reproductive systems of aquatic animals, and is carcinogenic and mutagenic. Therefore, in order to protect human health, it is urgent to establish a method for the determination of siloxane content in drinking water and source water.MethodsHerein, this paper proposes a precise, fast, and selective method using solid-phase microextraction combined with gas chromatography-mass spectrometry (GC-MS/MS) method for the simultaneous detection of 11 kinds of siloxanes in drinking water and source water. Quantification of siloxanes was carried out by internal standard method. The parameters that affect the extraction and desorption processes were optmised. The extraction efficiency of four commercially available SPME fibers was evaluated. The results showed that divinylbenzene/polydimethyl-siloxane or divinylbenzene/Carboxen/polydimethylsiloxane was the best coating for the extraction of siloxane.ResultsThis method provided good linearity (r > 0.9946) and precision (RSD% <8.0%) with the minimum detection mass concentration ranging from 0.008 to 0.025 μg/L under the optimized extraction and GC-MS/MS analysis conditions. The developed method has been applied to the simultaneous analysis of 11 kinds of siloxanes in drinking water and source water, and the results showed that decamethylcyclopentasiloxane (D5) and dodecamethylcyclohexasiloxane (D6) were found in two source water samples at concentrations ranging from 0.008 to 0.012 μg/L and 0.015–0.019 μg/L, respectively.ConclusionThis developed method was simple, quick, and effective and our satisfactory results demonstrated its suitability for the simultaneous determination of 11 kinds of siloxanes in drinking water and source water.